2019
DOI: 10.18203/2320-6012.ijrms20191331
|View full text |Cite
|
Sign up to set email alerts
|

A study on diagnostic efficacy of pulmonary imaging tool in patients with rheumatoid arthritis

Abstract: Background: Pulmonary complication in Rheumatoid arthritis is major health concern in the field of rheumatology. So this study is to find out the sensitive imaging tool for detecting different types of pulmonary changes seen in RA.Methods: This is a comparative, analytical, cross sectional, Institution- based, single centre study. We included all adult willing patients of Rheumatoid arthritis (age >18) and selected them based on 2010 ACR/EULAR criteria. Severity was assessed by number of joints involve in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
2
0
1
Order By: Relevance
“…As we had excluded known COPD patients, males were less in proportion in the present study when compared with other studies. In our study, it was observed that in most of the patients, disease duration was less than 2 years, and similar findings were observed in other published studies, 14,20 except for the study 21 from Turkey, where most of the patients had disease duration of more than 2 years. Among the symptomatic patients in our study, dyspnea was the most common complaint at presentation, followed by cough and wheezing.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As we had excluded known COPD patients, males were less in proportion in the present study when compared with other studies. In our study, it was observed that in most of the patients, disease duration was less than 2 years, and similar findings were observed in other published studies, 14,20 except for the study 21 from Turkey, where most of the patients had disease duration of more than 2 years. Among the symptomatic patients in our study, dyspnea was the most common complaint at presentation, followed by cough and wheezing.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, restrictive pattern was the most common abnormality. A similar trend was observed in other published studies 20,22,24 except for the study 23 conducted in the United States, where the obstructive pattern was the most common type of PFT abnormality. Higher incidence of smokers (58%) in that study might be the reason for the obstructive pattern being the most common pattern.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation